Acute lung injury in fulminant hepatic failure following paracetamol poisoning. Issue 4 (April 1995) - Baudouin, S V; Howdle, P; O'Grady, J G; Webster, N R
Abstract : BACKGROUND--There is little information on the incidence of acute lung injury or changes in the pulmonary circulation in acute liver failure. The aim of this study was to record the incidence of acute lung injury in fulminant hepatic failure caused by paracetamol poisoning, to document the associated pulmonary circulatory changes, and to assess the impact of lung injury on patient outcome. METHODS--The degree of lung injury was retrospectively assessed by a standard scoring system (modified from Murray) in all patients with fulminant hepatic failure caused by paracetamol poisoning, admitted to the intensive care unit over a one year period. The severity of liver failure and illness, other organ system failure, and patient outcome were also analysed. RESULTS--Twenty four patients with paracetamol-induced liver failure were admitted and nine developed lung injury of whom eight (33%) had severe injury (Murray score > 2.5). In two patients hypoxaemia contributed to death. Patients with lung injury had higher median encephalopathy grades (4 v 2 in the non-injured group) and APACHE II scores (29 v 16). Circulatory failure, requiring vasoconstrictor support, occurred in all patients with lung injury but in only 40% of those without. Cerebral oedema, as detected by abnormal rises in intracranial pressure, also occurred in all patients with lung injury but in only 27% of the non-injured patients. The incidence of renal failure requiring renal replacement therapy was similar in both groups (67% and 47%). Pulmonary artery occlusion pressures were normal in the lung injury group. Cardiac output was high (median 11.2 1/min), systemic vascular resistance low (median 503 dynes/s/cm-5), and pulmonary vascular resistance low (median 70 dynes/s/cm-5), but not significantly different from the group without lung injury. Mortality was much higher in the lung injury group than in the non-injured group (89% v 13%). CONCLUSIONS--Acute lung injury was common in patients with paracetamol-induced fulminant hepatic failure and was associated with systemic circulatory failure and cerebral oedema. The development of acute lung injury was associated with high mortality.